Talent management, home office and digital communication: Past, present… what post-COVID-19 future? - Félix Mateus, Anabela (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
SARS-CoV-2 has highlighted the need for Home Office with teleworking and the adaptation of companies to be able to communicate with their employees and to retain the better ones. Within the Talent Management scope their retention has become priority. Analyzing real cases, we found that using virtual communication and digital tools, teleworking is the preferred alternative for many. Platforms and networks help to establish bonds, create relationships and generate trust between leaders and other employees. Also allow greater flexibility. Remote work is attractive for employee performance and practices related to engagement and commitment promote Talent Retention and greater productivity.